Efektivitas Pelatihan Komputer dalam Meningkatkan Kemampuan Teknologi Guru SD: Analisis Berdasarkan Metode Wawancara: Penelitian - Rahmat; Sadly Syamsuddin; Erfan Hasmin; Arwansyah; Sitti Harlina; Arham Arifin; Hasyrif SY; Faizal; Imran Djafar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study evaluated the effectiveness of computer training in improving the technological skills of elementary school teachers at UPTD SDN 168 Inpres Jambua through a participatory evaluation approach. The training was conducted using the blended learning method, and the evaluation used questionnaires, focus group discussions (FGDs), interviews, and observations. The results showed significant improvement in teachers' technology skills. Participant feedback indicated that the relevant training materials and interactive methods were very effective. The findings confirmed the importance of continuous and participatory training and the need to adjust the training program based on participant feedback. Recommendations include increasing interactivity, adapting materials to technological developments and ongoing support for teachers. This study contributes to the development of more effective and sustainable technology training programs for primary school teachers.